2017
DOI: 10.1536/ihj.16-533
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Is Associated With Platelet Coagulation Function Rather Than Enzymatic Coagulation Function in Patients With Takayasu Arteritis

Abstract: SummaryThe integral changes of coagulation and fibrinolysis, and their relationships with inflammation in patients with Takayasu arteritis (TA) remain undetermined. The purpose of this study was to analyze the changes of coagulation and fibrinolysis process in patients with TA by thrombelastography (TEG).A total of 127 patients with TA and 55 healthy controls were enrolled. Patients with TA were grouped according to disease activity. The routine hematological parameters, traditional coagulation assays, and TEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…Inflammation-induced thrombosis and platelet dysfunction may be common in TA. In a study, patients with TA had higher levels of platelet P-selectin and plasma thromboxane B2, and lower plasma cyclic adenosine monophosphate levels than healthy subjects, which indicated increased platelet activity ( 135 ). Akazawa et al demonstrated that levels of β-thromboglobulin, thrombin/AT-III complex, fibrinopeptide A, and D-dimer are significantly higher in TA patients than in normal controls, reflecting a hypercoagulability state ( 136 ).…”
Section: Laboratory and Biomarkersmentioning
confidence: 99%
“…Inflammation-induced thrombosis and platelet dysfunction may be common in TA. In a study, patients with TA had higher levels of platelet P-selectin and plasma thromboxane B2, and lower plasma cyclic adenosine monophosphate levels than healthy subjects, which indicated increased platelet activity ( 135 ). Akazawa et al demonstrated that levels of β-thromboglobulin, thrombin/AT-III complex, fibrinopeptide A, and D-dimer are significantly higher in TA patients than in normal controls, reflecting a hypercoagulability state ( 136 ).…”
Section: Laboratory and Biomarkersmentioning
confidence: 99%
“…Удобным маркером оценки риска оказался высокий уровень С-реактивного белка [10]. В ряде случаев повышенный риск тромбозов при АТ ассоциировался с наличием волчаночного антикоагулянта и повышенной функцией тромбоцитов [11,12]. В то же время, назначение ацетилсалициловой кислоты в суточной дозе 100-335 мг сопровождалось уменьшением риска КВО АТ [13].…”
Section: Discussionunclassified
“…Поражение сердца при аутопсии было отмечено в 17 (77%) случаях. Масса сердца составила 325 (270-460) г, длина -10 (4-12) см, ширина -9 (8-10) см, толщина задней стенки левого желудочка (ЛЖ) -6 (1,5-9) мм, толщина стенки ЛЖ -15 (11)(12)(13)(14)(15)(16)(17)(18) мм, в одном случае толщина стенки ЛЖ достигала 22 мм. Ме толщины стенки правого желудочка составила 3 (1-4) мм.…”
Section: результатыunclassified
“…Takayasu arteritis patients were found to be in a hypercoagulable state when compared to controls Inflammation was associated with PLT coagulation rather than enzymatic coagulation; treatment should focus on anti-PLT therapy 206 KD R: # 208,209 K: # 208,209 No abnormal variables documented…”
Section: No Abnormal Variables Documentedmentioning
confidence: 99%
“…206 From this, it was concluded that the inflammation observed in Takayasu arteritis is a function of PLT activation rather than enzymatic coagulation and that anti-PLT treatment should be the focus of therapy. 206 This provides a prime example of how VETs can be used to redirect treatment of vasculitides and necessitates further study. Studies presented in Table 6 reveal hypercoaguable states associated with Kawasaki disease (KD), Behçet's disease (BD), microscopic polyangiitis, Henoch-Schönlein T A B L E 6 (Continued)…”
Section: No Abnormal Variables Documentedmentioning
confidence: 99%